A framework for the analysis of damage and recovery characteristics of asphalt mixtures. Issue 9 (2nd September 2021) - Sadeq, Mohammed; Huang, Chien-Wei; Masad, Eyad; Al-Khalid, Hussain; Sirin, Okan
ABSTRACT: This study presents two approaches for evaluating damage and recovery characteristics of asphalt mixtures. The first approach focuses on determining damage by extracting recoverable viscoelastic strain that has no damage and comparing it with the strain response of a material that has damage. The second approach is based on identifying the capacity of asphalt mixtures to recover some of the damage that may occur during creep loading. The advantage of these approaches is that they utilise experimental data to extract damage and recovery responses, without detailed mathematical modelling of material behaviour. The developed approaches are used to analyse the behaviours of fine aggregate mixtures (FAM) incorporating warm mix additives. The results show that these mixtures vary in their damage and recovery characteristics. For example, Sasobit FAM experienced the highest damage among mixtures, but it also had the highest recovery. Ageing was found to reduce the differences among mixtures in terms of resistance to damage, but it had less effect on the differences in their healing potential.